Predation pressure by avian predators suggests summer limitation of small‐mammal populations in the Canadian Arctic. Issue 1 (1st January 2014) - Therrien, J.-F.; Gauthier, G.; Korpimäki, E.; Bêty, J.
Abstract : Predation has been suggested to be especially important in simple food webs and less productive ecosystems such as the arctic tundra, but very few data are available to evaluate this hypothesis. We examined the hypothesis that avian predators could drive the population dynamics of two cyclic lemming species in the Canadian Arctic. A dense and diverse suite of predatory birds, including the Snowy Owl ( Bubo scandiacus ), the Rough‐legged Hawk ( Buteo lagopus ), and the Long‐tailed Jaeger ( Stercorarius longicaudus ), inhabits the arctic tundra and prey on collared ( Dicrostonyx groenlandicus ) and brown ( Lemmus trimucronatus ) lemmings during the snow‐free period. We evaluated the predation pressure exerted by these predators by combining their numerical (variation in breeding and fledgling numbers) and functional (variation in diet and daily consumption rates) responses to variations in lemming densities over the 2004–2010 period. Breeding density and number of fledglings produced by the three main avian predators increased sharply without delay in response to increasing lemming densities. The proportion of collared lemmings in the diet of those predators was high at low lemming density (both species) but decreased as lemming density increased. However, we found little evidence that their daily consumption rates vary in relation to changes in lemming density. Total consumption rate by avian predators initially increased more rapidly for collared lemming but eventually leveled off at a much higher value for brown lemmings, the most abundant species at our site. The combined daily predation rate of avian predators exceeded the maximum daily potential growth rates of both lemming species except at the highest recorded densities for brown lemmings. We thus show, for the first time, that predation pressure exerted without delay by avian predators can limit populations of coexisting lemming species during the snow‐free period, and thus, that predation could play a role in the cyclic dynamic of these species in the tundra.